Outpatient Treatment of Lyme Disease. Issue 5 (May 2023) - Fuchs, Susan
Abstract: Lyme disease, also called Lyme borreliosis, is caused by the spirochete Borrelia burgdorferi sensu stricto ( B burgdorferi ) in the Upper Atlantic Coast and Borrelia mayonii in the Upper Midwest and West Coast. It can cause a range of manifestations including erythema migrans, cranial nerve palsies, meningitis, carditis, and arthritis. Recent guidelines advocate for outpatient treatment for many of these conditions. Scenarios will be presented that outline treatment of these manifestations.